2019
DOI: 10.3390/ijerph16101728
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Patient Outcomes Associated with Use of Emergency Medical Services Operating in Urban Versus Rural Areas: A Systematic Review

Abstract: The goal of this systematic review was to examine the existing literature base regarding the factors impacting patient outcomes associated with use of emergency medical services (EMS) operating in urban versus rural areas. A specific subfocus on low and lower-middle-income countries was planned but acknowledged in advance as being potentially limited by a lack of available data. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed during the preparation of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 50 publications
(73 reference statements)
6
41
0
1
Order By: Relevance
“…However, we observed that the overall median time from EMS call to EMS arrival on scene was similar to that of other developed countries as a recent systematic review to determine EMS response time showed that Asia, America, and Europe had median response times ranging from 7 to 11 min . A previous systematic review showed significantly shorter transport times in urban areas than rural areas, whereas the median time to hospital arrival in the most populated region in Japan, the Kanto region, was the longest . Multiple potential factors could affect the time to hospital arrival, such as patient age and the distribution of medical institutions and specialized hospitals, such as stroke centers …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, we observed that the overall median time from EMS call to EMS arrival on scene was similar to that of other developed countries as a recent systematic review to determine EMS response time showed that Asia, America, and Europe had median response times ranging from 7 to 11 min . A previous systematic review showed significantly shorter transport times in urban areas than rural areas, whereas the median time to hospital arrival in the most populated region in Japan, the Kanto region, was the longest . Multiple potential factors could affect the time to hospital arrival, such as patient age and the distribution of medical institutions and specialized hospitals, such as stroke centers …”
Section: Discussionsupporting
confidence: 66%
“…16 A previous systematic review showed significantly shorter transport times in urban areas than rural areas, whereas the median time to hospital arrival in the most populated region in Japan, the Kanto region, was the longest. 17 Multiple potential factors could affect the time to hospital arrival, such as patient age and the distribution of medical institutions and specialized hospitals, such as stroke centers. 18 Furthermore, combining prehospital data with external data resources could be beneficial in further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This sample therefore does not appear representative of the Saudi citizen population which is approximately 51% male and 49% female (18), but an accurate gender breakdown via each region is difficult to ascertain from national data. It is also worth noting that while there is a significant gender imbalance in non-Saudi nationals (18), largely composed of male workers from other countries, this cohort may instead access an alternative EMS to Red Crescent (13,15). As this was a cross-sectional study, it was not possible to ascertain the precise reasons for this skew, however it is consistent with a previous study in Turkey that showed males use EMS at a higher rate than females (19).…”
Section: General Demographic Datasupporting
confidence: 80%
“…Similarly, little research has focused on rural EMS outside of the United States, Europe and Australia, with minimal focus on countries in Asia, Africa or the Middle-East. [ 12 ] This lack of research on rural EMS delivery in such locations is an area of need, as the significant service delivery, cultural, geographic and economic differences mean that findings from research in Western countries cannot necessarily be generalized to these settings.…”
Section: Introductionmentioning
confidence: 99%